2017
DOI: 10.2135/cropsci2017.03.0159
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Characterization of Stem Rust Resistance in a Global Spring Wheat Germplasm Collection

Abstract: Stem rust, caused by the fungus Puccinia graminis Pers. f. sp. tritici Ericks, is one of the most damaging diseases of wheat (Triticum aestivum L.). The recent emergence of the stem rust Ug99 race group poses a serious threat to world wheat production. Utilization of genetic resistance in cultivar development is the optimal way to control stem rust. Here, we report association mapping of stem rust resistance in a global spring wheat germplasm collection (2152 accessions) genotyped with the wheat iSelect 9K sin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
18
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 73 publications
3
18
1
Order By: Relevance
“…In our study, LD decay was found strongly different in the three genomes with B genome to have the quickest decay followed by A genome, which is supported by previous reports (Gao et al, 2017;Riaz et al, 2018). This supports the practical use of D genome markers suitable for association tests even though less in number (Gao et al, 2017). D genome was found to have the highest LD than other genomes which has also been mentioned in several previous studies (Nielsen et al, 2014;Wang et al, 2014;Zegeye et al, 2014;Voss-Fels et al, 2015;Riaz et al, 2018).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…In our study, LD decay was found strongly different in the three genomes with B genome to have the quickest decay followed by A genome, which is supported by previous reports (Gao et al, 2017;Riaz et al, 2018). This supports the practical use of D genome markers suitable for association tests even though less in number (Gao et al, 2017). D genome was found to have the highest LD than other genomes which has also been mentioned in several previous studies (Nielsen et al, 2014;Wang et al, 2014;Zegeye et al, 2014;Voss-Fels et al, 2015;Riaz et al, 2018).…”
Section: Discussionsupporting
confidence: 90%
“…It has an added advantage of capturing information on germplasm derived from secondary and tertiary gene pools as the array is developed using exome capture of wheat and its wild relatives (Allen et al, 2017;Rasheed and Xia, 2019). In our study, LD decay was found strongly different in the three genomes with B genome to have the quickest decay followed by A genome, which is supported by previous reports (Gao et al, 2017;Riaz et al, 2018). This supports the practical use of D genome markers suitable for association tests even though less in number (Gao et al, 2017).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Previously, Sr11 was reported to be effective to race TKTTF and present in Ethiopian wheat germplasm (Nirmala et al 2016 ). Association mapping studies have confirmed the presence of Sr7a, which confers resistance to race TKTTF, and Sr8a, which confers resistance to TRTTF, in conventional germ-plasm (Bajgain et al 2015 ; Gao et al 2017 ; Mihalyov et al 2017 ). Although nearly all of the bread wheat lines were resistant to race JRCQC, the genes specifically responsible for conferring this resistance are unknown.…”
Section: Discussionmentioning
confidence: 97%
“…Though several studies have evaluated seedling and/or field response of wheat association mapping panels to Pgt isolates (Yu et al, 2011 , 2012 ; Letta et al, 2014 ; Zhang et al, 2014 ; Gao et al, 2017 ; Mihalyov et al, 2017 ; Muleta et al, 2017 ), only one has evaluated field response of the wheat population studied to more than one Pgt race (Chao et al, 2017 ). In that study, field response of a bulk of six Pgt isolates in Minnesota was compared to response to a bulk of Pgt isolates in Ethiopia, and differences between these datasets could be due to environment and/or race.…”
Section: Discussionmentioning
confidence: 99%